COMPARATIVE STUDY OF THE CASUALTY ANODE CATHODIC PROTECTION SYSTEM BETWEEN ZINC ANODE (Zn) AND ALUMINUM ANODE (AI) IN KRI TJA-541 - Pompy Pratisna; Dueng Deriva; Nova Wahyu Permana (Politeknik Negeri Madura, 2025)
Seawater corrosion is one of the main causes of damage to the hull and hull of the ship, which can reduce the strength, service life, and safety of the ship and crew. To prevent losses due to corrosion, protection of the hull plate is required through two methods: passive protection (coating) and active protection (cathodic protection). A commonly used method in active protection is the victim anode system, in which more reactive metals are sacrificed to protect hull metal. The anodes that are often used are zinc (Zn) and aluminum (Al). This study aims to evaluate the efficiency and effectiveness of the anode system installed in KRI TJA-541, by comparing the needs of the victim anode from a technical and economic perspective, as well as the results of theoretical calculations based on the DNV RP-B401 standard. The observation results showed that the thickness of the coating of KRI TJA-541 ranged from 150-250 ?m, which is included in category II (DNV RP-B401), with a Zn anode requirement of 439 kg or Al 153 kg. Currently, 1424 kg of Zn is installed, which shows that the use of the DNV RP-B401 standard with aluminum (Al) anode is more technically and economically advantageous. Keywords: Cathodic Protection, Victim Anode, DNV RP-B401, KRI TJA-541